Bsheer, Rossie. Archive Wars: The Politics of History in Saudi Arabia. Stanford: Stanford University Press, 2020 - Pietrasik, Kamil (Archiwa – Kancelarie – Zbiory, 2021)
Recenzja Bsheer, Rossie. Archive Wars: The Politics of History in Saudi Arabia. Stanford: Stanford University Press, 2020